Effectiveness of carbazochrome sodium sulfonate in reducing hemorrhage during TURP for BPH: A systematic review - Fazri, Akhmad Miftahudin; Widyasmara, Her Bayu; Rachman, Bagus Taufiqur; Adityagama, Miftah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Evidence from the past five years has highlighted increasing interest in pharmacological adjuncts at improving transurethral resection of the the prostate (TURP). Both randomized controlled trials (RCTs) and observational research have investigated the role of carbazochrome sodium sulfonate (CSS), with varying results. This systematic review aimed to evaluate the effectiveness of CSS in transurethral resection of the prostate (TURP) for benign prostatic hyperplasia (BPH). The review was conducted in accordance with the Prefrred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A comprehensive search of Embase, PubMed/MEDLINE, Scopus, Web of Science, and the Cochrane Library was performed. Eligible studies included cohort studies, case-control methodologies, and RCT investigations related to CSS in TURP procedures and reporting outcomes such as blood loss and complications. Five RCTs comprising a total of 550 participants met the inclusion criteria. The findings indicated that CSS was associated with a significant reduction in intraoperative bleeding compared with tranexamic acid (TXA). Across all studies, CSS exhibited a favorable safety profile, with no severe adverse effects reported. CSS appears to be a promising advancement in managing perioperative bleeding during TURP procedures for BPH. Its hemostatic efficacy and safety profile suggest potential benefits for surgical outcomes and patient recovery. Nevertheless, further high-quality, large-scale studies are warranted to establish standardized treatment protocols and to clarify optimal role of CSS in contemporary urological practice.